Endophytic Phomopsis sp. colonization in Oryza sativa was found to result in plant growth promotion and piperine production. Issue 4 (5th June 2017) - S, Chithra; B, Jasim; Mathew, Jyothis; Radhakrishnan, E K
Abstract : Endophytic fungi have been reported to have the acquired ability to synthesize host plant specific medicinal natural products. Many fungi with such properties have been characterized and optimized for the conditions which favor maximal production of desired products. However, the inherent plant colonization property of promising endophytic fungi is least studied. Exploiting the transgenome functioning of these fungi have immense applications to add beneficial features to nonhost plants. In the present study, the endophytic fungus Phomopsis sp. isolated from Piper nigrum was confirmed for piperine production by HPLC and LCMS/MS. Further, the fungal isolate was studied for its colonization ability in Oryza sativa . Interestingly, the fungi treated plants were found to have significant plant growth enhancement when compared to the control. Further screening of extract from treated plants by HPLC and LCMS/MS resulted in the confirmation of presence of piperine. The observed result is extremely significant as it opens up novel applications of endophytic fungal colonization in taxonomically diverse plants.